2021
DOI: 10.1177/11206721211001275
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis of macular edema after cataract surgery in diabetic patients, topical Nepafenac versus intravitreal Ranibizumab

Abstract: Purpose: To compare effect of topical Nepafenac versus intravitreal Ranibizumab on macular thickness after cataract surgery in diabetic patients with no preoperative macular edema. Patients and methods: A prospective randomized controlled study recruited diabetic patients with visually significant cataract and no diabetic macular edema (DME). Patient underwent uncomplicated phacoemulsification with IOL implantation and were randomly assigned to receive post-operative topical Nepafenac, intra-operative intravit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
(20 reference statements)
1
5
0
Order By: Relevance
“…Our study showed that the combined ranibizumab/ laser photocoagulation therapy has high application value and is superior to ranibizumab and laser monotherapies. Combined treatment is more effective in alleviating clinical symptoms, improving visual acuity, and reducing the occurrence of complications in patients with DME, which is basically consistent with Ishibashi et al 12 , Berger et al 13 , and Mitchell et al 14 Howaidy et al 10 used laser therapy and ranibizumab to treat patients with DME on the basis of routine intervention, and showed that it can effectively reduce the thickness of the macular fovea and prevent the occurrence of related complications, which is consistent with the results of our study. Ranibizumab has numerous advantages such as strong specificity, high bioavailability, and strong permeability, and can effectively inhibit VEGF in the retina, prevent vascular leakage, and reduce retinal edema.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our study showed that the combined ranibizumab/ laser photocoagulation therapy has high application value and is superior to ranibizumab and laser monotherapies. Combined treatment is more effective in alleviating clinical symptoms, improving visual acuity, and reducing the occurrence of complications in patients with DME, which is basically consistent with Ishibashi et al 12 , Berger et al 13 , and Mitchell et al 14 Howaidy et al 10 used laser therapy and ranibizumab to treat patients with DME on the basis of routine intervention, and showed that it can effectively reduce the thickness of the macular fovea and prevent the occurrence of related complications, which is consistent with the results of our study. Ranibizumab has numerous advantages such as strong specificity, high bioavailability, and strong permeability, and can effectively inhibit VEGF in the retina, prevent vascular leakage, and reduce retinal edema.…”
Section: Discussionsupporting
confidence: 81%
“…As a result, the retina is in a dry state, which provides ideal conditions for laser photocoagulation treatment, ensures good spot response under low laser energy state, and reduces the occurrence of bleeding and other related complications. 10,15,16 Mi et al 11 also confirmed that the combination of ranibizumab and micro pulse laser therapy can reduce the number of anti-VEGF drug injections and relieve the pain and psychological burden of patients.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In all, a total of 2566 participants from 17 randomized controlled trials were included in the finally network meta-analysis ( Table 1 and Supplementary Table 1). 9 , 10 , 13 , 14 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 17 studies reported 5 perioperative interventions: topical steroid eye drop, topical NSAIDs eye drop, intravitreal anti-VEGF agents injection, intravitreal steroid injection, and sub-tenon steroid injection. All studies used no intervention or topical steroid eye drop alone (None/Topical Steroids) as reference treatments.…”
Section: Resultsmentioning
confidence: 99%
“…The safety and efficacy of topical nepafenac 0.1% were tested in 6 eyes of 5 patients with DME, which showed that topical nepafenac treatment improved vision and decreased retinal thickness [ 211 ]. Postoperative topical nepafenac was shown to be effective for prophylaxis of macular edema in diabetic patients underwent phacoemulsification and intraocular lens implantation [ 212 ]. Further investigations on whether topical NSAIDs could serve as an alternative or adjunctive treatment to intravitreal anti-VEGF therapy are required.…”
Section: Therapeutic Strategies For Dmementioning
confidence: 99%